A virtual maintenance-based approach for satellite assembling and troubleshooting assessment. (September 2017) - Geng, Jie; Li, Ying; Wang, Ranran; Wang, Zili; Lv, Chuan; Zhou, Dong
Abstract: In this study, a Virtual Maintenance (VM)-based approach for satellite troubleshooting assessment is proposed. By focusing on various elements in satellite assemble troubleshooting, such as accessibility, ergonomics, wiring, and extent of damage, a systematic, quantitative, and objective assessment model is established to decrease subjectivity in satellite assembling and troubleshooting assessment. Afterwards, based on the established assessment model and satellite virtual prototype, an application process of this model suitable for a virtual environment is presented. Finally, according to the application process, all the elements in satellite troubleshooting are analyzed and assessed. The corresponding improvements, which realize the transformation from a conventional way to a virtual simulation and assessment, are suggested, and the flaws in assembling and troubleshooting are revealed. Assembling or troubleshooting schemes can be improved in the early stage of satellite design with the help of a virtual prototype. Repetition in the practical operation is beneficial to companies as risk and cost are effectively reduced. Highlights: A novel virtual application for satellite troubleshooting assessment method is presented. Satellite troubleshooting assessment is conducted in the satellite design stage. The assessment is conducted via non-immersive and immersive virtual maintenance. The assessment is conducted by static check and dynamic simulation. The method assesses the qualitative factors quantitatively.